KODE ETIK KONSELING SERTA PERMASALAHAN DALAM PENERAPANNYA - Jumrawarsi Jumrawarsi; Mudjiran Mudjiran; Neviyarni Neviyarni; Herman Nirwana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Everyone is required to be able to adapt to the existing revolution. Problems can arise if the person is not able to adapt well. This can be used by problem counselors to provide services to people who have problems. Consultants must adhere to a code of ethics when providing one's services. Various problems can arise when implementing a code of ethics in counseling services, both from the counselor and the client. Awareness needed by consultants in order to run well, competence increases, and policies and supervision are directed.